AKTIVITAS BUDAYA SEKOLAH BERBASIS KARAKTER IKHWANUL MUSLIMIN (STUDI ETNOGRAFI PADA SIT BINA ILMI PALEMBANG) - Yuniar Thohir (Tadrib: Jurnal Pendidikan Agama Islam, 2020)
This paper describes, analyzes and interprets cultural activities developed at SIT Bina Ilmi Palembang to later discover the concept of Integrated Islamic School culture that can shape student characters. This research was a case study in an ethnographic framework. The research informants were the director of SIT Bina Ilmi, school principals, teachers, students, librarians, school assistants, canteen traders, the parents of students and the residents around the school determined previously by purposive sampling. The data were collected by having observation, interview and documentation techniques. The data were then analyzed by combining the Creswell model and Mathew and Hubermen, namely by performing three stages namely, data reduction (date reduction), data display (date display) / description, and interpretation/verification of data. To check the validity of the data, triangulation, member chacking and extension of the observation were carried out. The results showed that the school cultural activities developed at this SIT were routine activities: which included: (1) classroom learning processes (2) extra-curricular activities: Islamic personal development (3) social activities in the community: visits to orphanages, social service and munāṡoroh. Through the school culture it is hoped that the established educational goals will be achieved which are adaptations of the Ikhwanul Muslimin's muwashofat concepts, namely religious worship, matinul khuluq, mutsaqquful fikri, mujahadatun linafsihi, nafi'un lighoirihi. Finally, the findings of this research are the Ikhwanul Muslimin concept which is the basis of the cultural development of SIT Bina Ilmi Palembang.